The Effect of Recruitment, Selection, and Training on Employee Performance at PT Darium Abadi - Dwi Utami; Hendra Galuh; Abdul Rauf; Atik Atikah; Yanthi Meitry Gunawan (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose of the study was to determine the effect of Recruitment, Selection, and Training on Employee Performance at PT Darium Abadi, partially or simultaneously. Research using associative methods with a quantitative approach. The sample was 94 people. Data collection techniques and tools with questionnaires. Inferential statistical analysis techniques for hypothesis testing. Data processing with SPSS version 25. Research results (1) Recruitment has a positive and significant impact on employee performance. A good recruitment process helps companies find employees who fit their needs, thereby improving overall performance. (2) Selection shows a positive and significant influence on employee performance. A careful selection process ensures only candidates who meet the criteria are accepted, thereby increasing work effectiveness and productivity. (3) Training exerts the most positive influence on employee performance. Structured training helps improve employees' technical skills, efficiency, and motivation, which has a direct impact on work quality and productivity. (4) Simultaneously, the three variables have a positive and significant effect on employee performance. This research confirms the importance of integrated HR management to achieve optimal employee performance. Recruitment, selection, and training are three key elements that are interrelated in influencing employee performance at PT Darium. These three processes work in concert.